2018
DOI: 10.2991/j.jegh.2018.08.102
|View full text |Cite
|
Sign up to set email alerts
|

Sex and Gender Differences in Acute Pediatric Diarrhea: A Secondary Analysis of the DHAKA Study

Abstract: Pediatric diarrheal disease is a significant source of morbidity and mortality in the developing world. While several studies have demonstrated an increased incidence of diarrheal illness in boys compared with girls in low-and middle-income countries (LMIC), the reasons for this difference are unclear. This secondary analysis of the dehydration: assessing kids accurately (DHAKA) derivation and validation studies included children aged <5 years old with acute diarrhea in Dhaka, Bangladesh. The dehydration statu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
13
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 20 publications
(36 reference statements)
4
13
1
3
Order By: Relevance
“…However, the children's health status including mortality and chronic morbidity of the BG region was still relatively poor, which might be aligned with the poor socioeconomic condition of the region. The children's illness incidence experience seemed to be not extremely high or low compared to the illness experience of other similar low-income countries such as Dhaka in Bangladesh, 14 little lower in case of diarrhea incidence than previous studies in Ethiopia. [15][16][17] U5 mortality were similar in other rural areas in neighborhood countries in East Africa 18 while it is a litter lower than previous study period in the BG region even if it is still now low enough to be accepted.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…However, the children's health status including mortality and chronic morbidity of the BG region was still relatively poor, which might be aligned with the poor socioeconomic condition of the region. The children's illness incidence experience seemed to be not extremely high or low compared to the illness experience of other similar low-income countries such as Dhaka in Bangladesh, 14 little lower in case of diarrhea incidence than previous studies in Ethiopia. [15][16][17] U5 mortality were similar in other rural areas in neighborhood countries in East Africa 18 while it is a litter lower than previous study period in the BG region even if it is still now low enough to be accepted.…”
Section: Discussioncontrasting
confidence: 70%
“…The average monthly household income was 1,771 Birr (63 USD equivalent). The average number of family members was 6 (range, [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. Most common material of the roof of the dwelling unit was thatch/mud (53.5%) and the floor of it was earth/sand (88.6%).…”
Section: Resultsmentioning
confidence: 99%
“…This finding supported a cross-sectional study conducted in Ethiopia that showed boys have 2.52 times higher odds of having acute diarrhea as compared with girls. 39 A recent study from Palestine 40 and Bangladesh 41 also reported similar findings. “Despite several studies demonstrating an increased incidence of diarrheal illness in boys compared with girls in many developing countries, the reason for this difference remains unclear.” 41 Researchers hypothesized that the variance may be due to gender-based factors, such as sex-based biological factors, environmental, and cultural factors.…”
Section: Discussionmentioning
confidence: 61%
“… 39 , 40 The biological hypothesis assumes that there may exist pathophysiologic sex differences between girls and boys with regard to acute diarrhea that make boys more susceptible. 34 , 41 …”
Section: Discussionmentioning
confidence: 99%
“…Most (59.3%) sporadic cases were associated with children ≤ 5 years, which concurs with several previous studies [ 3 , 7 ]. Within the ≤ 5 years cohort, cases were more frequently associated with male children (OR 1.3873), potentially reflecting the tendency of male children to mount weaker immune responses [ 21 ], an enhanced susceptibility to environmental exposures via gender-related outdoor activities [ 22 ], or a gender-related bias in healthcare-seeking behaviours [ 23 ]. Conversely, female children were statistically associated with outbreak-related cryptosporidiosis, potentially reflecting higher levels of direct contact (and subsequent transmission) between parents/family members and female children [ 24 ].…”
Section: Discussionmentioning
confidence: 99%